EVALUATION OF THE CULTURE PERFORMANCE OF VANNAMEI SHRIMP (LITOPENAEUS VANNAMEI) IN AN INTENSIVE FERMENTATION-BASED SYSTEM OF CV 58 IN NORTH BALI - Manurung, Vetricia Monalisa; Martini, Ni Nyoman Dian; Yudasmara, Gede Ari (Jurusan Perikanan dan Kelautan, 2025)
Intensive vannamei shrimp (Litopenaeus vannamei) farming using a fermentation-based system offers an innovative solution to environmental management and production efficiency. This study was conducted over one cultivation cycle (80 days) in six ponds operated by CV Tambak 58, North Bali, integrating periodic probiotic fermentation. Key parameters evaluated included growth (ABW, ADG), feed efficiency (FCR), survival rate (SR), water quality, and microbiological stability. Results showed high productivity (up to 2.53 kg/m²), low FCR (1.13–1.40), and SR >85%, accompanied by stable planktonic and microbial communities. These findings indicate that fermentation-based systems reduce environmental stress and disease risks while enhancing the sustainability of intensive shrimp aquaculture